Engineering hydrology today conference organized by the Institution of Civil Engineers, the International Hydrological Decade Committee and the Institute of Hydrology, 18-20 February 1975. (Institution of Civil Engineers, 1975)
Broken down into six sessions, this work discusses water and water management, estimates irrigation needs and frequency flows and assesses surface water sources. Sir Norman Rowntree provides a valuable overview of the topic.